Ectopic decidual reaction mimicking peritoneal tubercles: A report of three cases - Shukla Shailaja; Pujani Mukta; Singh Sanjeet (Wolters Kluwer Medknow Publications, 2008)
Ectopic decidual reaction is commonly seen in the ovary and cervix; however, peritoneal localization is rare. Peritoneal deciduosis is usually an incidental histological finding. It may present a diagnostic dilemma by mimicking grossly peritoneal carcinomatosis or tubercles and deciduoid mesothelioma, microscopically. We report three cases of ectopic decidual reaction discovered incidentally during caesarian sections, as whitish yellow nodules resembling tubercles. Histology revealed extensive decidualisation. To the best of our knowledge, this is the first report of ectopic decidua mimicking peritoneal tubercles.